Robust fault estimation for uncertain switched linear systems with time-varying delay - Zhong, Yan-ke; Chen, Te-fang; Chen, Chun-yang (Journal of Central South University, 2015)
The problem of fault estimation is investigated for a class of uncertain switched systems with time-varying delay. A robust observer-based fault estimator is designed such that the augment error system is exponentially stable and the H ∞ performance index meets the predefined requirements. Based on the multiple Lyapunov-Krasovskii functions and the average dwell-time method, the delay dependent sufficient conditions on the existence of desired fault estimator are established. However, since these conditions are not linear matrix inequalities (LMIS), they can not be solved by MATLAB. By using a novel method, these conditions are presented in terms of LMIS. Finally, a numerical example is carried out. The designed fault estimator could tract the fault signal timely. Besides, the error between estimation and fault is very small. Therefore, the validity of the obtained results is illustrated.